Radial and ulnar approach for carotid artery stenting with Roadsaver™ double layer micromesh stent: Early and long‐term follow‐up. Issue 1 (7th December 2022) - Petkoska, Danica; Zafirovska, Biljana; Vasilev, Ivan; Novotni, Gabriela; Bertrand, Olivier F.; Kedev, Sasko
Abstract: Aims: We aimed to evaluate the feasibility and safety of carotid artery stenting (CAS) with a newly designed double‐layer micromesh stent using wrist approach in patients with significant carotid disease. Materials and Methods: Between January 2016 and December 2021, 105 patients undergoing CAS with Roadsaver™ stent were enrolled in a single center prospective study. Follow‐up assessments included neurological exams, duplex ultrasound (DUS), and 12‐lead ECG. The primary endpoint was the 30‐day composite rate of stroke, death, and myocardial infarction. Secondary endpoints included procedure success, access site complications, device success, target lesion revascularization, and in‐stent restenosis evaluated with DUS. Long‐term outcomes up to 72 months of follow‐up were assessed in all eligible patients. Results: The study population was predominantly male (69.5%) with a median age of 68 ± 8 years. Patients were symptomatic in 80% of the cases, and 35% fulfilled the high‐risk criteria for surgical endarterectomy. The right internal carotid artery was the target artery in 56 (53.4%), and the left in 49 (46.6%) of the cases. All procedures were successfully completed from the right wrist, with right radial access in 94 (89.5%) cases and ulnar artery access with previous radial artery occlusion in 11 (10.5%) cases. All patients were treated successfully with the study device. The primary endpoint was met with a 30‐day major adverse event rate of 0.9% (1/105). Up to 72 months of follow‐up (median 30 ± 20 months) there were no strokes, neurological deaths, or target lesion revascularization of the treated lesion. Doppler ultrasound examination revealed nonsignificant in‐stent restenosis in two asymptomatic patients. There was no hand ischemia detected in any patient. Conclusion: Results from this study demonstrate the radial and ulnar access for CAS with double layer micromesh Roadsaver™ stent is safe and feasible and associated with favorable early and long‐term follow‐up.